Literature and politics in the english reformation. (Politics, culture, and society in early modern Britain., 2017)
This book is a study of the English Reformation as a political and literary event. Focusing on an eclectic group of texts, unified by their explication of the key elements of the cultural history of the period 1510-80 the book unravels the political, poetic and religious themes of the era. Through readings of work by Edmund Spenser, William Tyndale, Sir Thomas More and John Skelton, as well as less celebrated Tudor writers, Betteridge surveys pre-Henrician literature as well as Henrician Reformation texts, and delineates the literature of the reigns of Edward VI, Mary Tudor and Elizabeth I. Ult.